The Effect Of Green Marketing, Green Product And Trust On Purchase Decisions At KFC BIM Bengkulu City - Julela Fitaloka; Merta Kusuma (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study aims to determine the effect of Green Marketing and Green Product and consumer trust on purchasing decisions at KFC BIM Bengkulu City. The population used in this study were all consumers at KFC BIM Bengkulu City, the number of samples used was 75 respondents, using incidental techniques. sampling is the number of indicators times 5. Data collected using the Classical Assumption Test Technique, Multiple Regression Analysis Techniques, Coefficient of Determination Analysis (R2), and Partial Test (t-test), Simultaneous Test (f-test) The results of this study indicate that partially Green Marketing has a significant effect on purchasing decisions, H1 influence of Green marketing on purchasing decisions at KFC BIM Bengkulu City, H2 influence of Green products on purchasing decisions at KFC BIM Bengkulu City. H3 influence of consumer trust on purchasing decisions at KFC BIM Bengkulu City. While the f-test of Green Marketing (X1), Green Product (X2) and Trust (X3) have a significant influence on purchasing decisions (Y) at KFC BIM Bengkulu City . . Based on a total of 15,211 with a Ftable value of 2.73, namely (15.211 > 2.73) and (sig < = 0.000 < 0.05) it can be said that H4 is simultaneously accepted by the variables of green marketing, green product and trust have a significant effect on purchasing decisions at KFC BIM....